Algorithms for extracting the QRS complex from the ECG (Texas Journal of Medical Science, 2026)
ECG is a diagnostic signal recorded on the patient's body at standard electrode locations, which reflects the electrical activity of the heart muscle. One of the main features of the ECG is a pulse waveform called the QRS complex. This complex corresponds to the time of depolarization of the heart ventricles and is of important diagnostic importance.